THE POWER OF SOCIAL MEDIA AS A DRIVE TO THE ADOPTION OF ETHICS IN THE CORPORATE PROMOTION - Sukkar, Amr; ElNashar, Ghada (International Journal For Research In Business, Management And Accounting, 2021)
The aim of this paper is to discuss how the social media can affect the corporate promotion ethics. The researchers investigated the moral principles and standards that establish the values and practices of the corporate social responsibility. This research explored several case studies where corporations had to give up promotional campaigns for the sake of ethics. The Qualitative methodology; comparative case study method implemented in this research studied a complex phenomenon of correlation between social media, ethics and corporate social responsibility. The paper found that the organizations should put into considerations the social variables that could harm their reputations during the implementation of their promotional campaigns. This paper explored the effect of ignoring the corporate social responsibility (CSR) concept of publishing and promoting impacts on corporate notoriety and brand value. The impacts of corporate social responsibility (CSR) activities on brand value advanced powerful promotions impacts. This ponder contributes the writing by unequivocal characterizing the promoting impacts of corporate social responsibility (CSR) activities.